Information literacy programs in the digital age : (Association of College and Research Libraries, 2007)
The book gathers the practice of information literacy in the university libraries in the United States. Information literacy progam is flexible it may be integrated into distance education or web-based instruction. The program is also embedded into discipline courses or a general education requirement